Micromotives of Vote Switchers and Macrotransitions: The Case of the Immigration Issue in a~Regional Earthquake Election in Germany 2018 - Paul W. Thurner; André Klima; Helmut Küchenhoff; Ingrid Mauerer; Stefan Mang; Melanie Walter-Rogg; Tassilo Heinrich; Thomas Knieper; Joachim Schnurbus (Politische Vierteljahresschrift, 2022)
Which issue-related motives underlie voters' decision to switch parties at the polls? Do switchers stick to the newly chosen party, or do they oscillate in a~short-term way at intermediate elections? Relying on the behavioral theory of elections, we assumed aspiration-based voting of boundedly rational voters. We elicited issue-related switch and stay motives in an open-ended survey question format to identify the individual dominant aspirational frame. We traced the respondents' voting trajectories over three consecutive elections, including two state (2013 and 2018) elections in Bavaria (Germany) and one German federal election (2017). We focused on one of the most polarizing and salient issues in these elections, namely immigration. The case of reference is the 2018 Bavarian state election. Here, the incumbent majoritarian center-right party Christian Social Union tried to deter the entry of the right-wing populist party Alternative for Germany by adapting to it on the immigration issue in tone and position. The selected case allows assessment of the impact of issue-based adaptive behavior of the incumbent party at the level of the voters' switch or stay choices. We estimated the direction and number of voter flows for two interelection sequences of different lengths between different types of polls (federal and state). Our transition estimates are based on the hybrid multinomial Dirichlet model, a~new technique integrating individual-level survey data and official aggregate data. Our estimates uncover substantial behavioral differences in the immigration issue public. – – Welche themenbezogenen Motive liegen der Entscheidung der Wähler zugrunde, die Partei an der Wahlurne zu wechseln? Bleiben die Wechselwähler bei der neu gewählten Partei, oder oszillieren sie bei Zwischenwahlen kurzfristig? Auf der Grundlage der "Behavioral Theory of Elections" gehen wir von einer aspirationsbasierten Wahlentscheidung begrenzt rationaler Wähler aus. Es werden themenbezogene Wechsel- und Bleibemotive in einem offenen Umfrageformat erhoben, um den individuell dominanten Aspirationsrahmen zu identifizieren. Wir verfolgen das Wahlverhalten der Befragten über drei aufeinanderfolgende Wahlen, darunter zwei Landtagswahlen (2013 und 2018) in Bayern (Deutschland) und eine Bundestagswahl (2017). Dabei konzentrieren wir uns auf eines der am stärksten polarisierenden und salienten Themen bei diesen Wahlen, nämlich die Zuwanderung. Anwendungsfall ist die bayerische Landtagswahl 2018. Hier versuchte die amtierende Mitte-Rechts-Partei CSU, den Einzug der rechtspopulistischen Partei AfD zu verhindern, indem sie sich in der Zuwanderungsfrage in Ton und Position an sie anpasste. Der ausgewählte Fall ermöglicht es, die Auswirkungen des themenbezogenen Anpassungsverhaltens der alleinregierenden Partei auf der Ebene der Wechsel- und Bleibeentscheidungen der Wähler zu bewerten. Wir schätzen die Richtung und den Umfang der Wählerströme für zwei unterschiedlich lange Sequenzen zwischen verschiedenen Wahlgängen (auf Bundes- und Landesebene). Unsere Schätzungen der Wechselwähler basieren auf einer neuen Technik, die Umfragedaten auf individueller Ebene und offizielle Aggregatdaten integriert, dem Hybrid-Multinomial-Dirichlet-Modell. Unsere Schätzungen decken erhebliche Verhaltensunterschiede in dem Issue Public Immigration auf.
Keywords: 320; Switching motives; Open-ended question; Hybrid multinomial Dirichlet model; Federal elections in Germany; Bavarian State election 2018; Right-wing populist parties; Motive der Wechselwahl; Offene Frage; Hybrides Multinomiales Dirichletmodell; Bayerische Landtagswahl 2018; Rechtspopulistische Parteien